Robust crop water simulation using system dynamic approach for participatory modeling. (January 2021) - Poulose, Thomas; Kumar, Saurav; Ganjegunte, Girisha K.
Abstract: A system dynamic model, SMITUV (System Dynamic Modeling of Infiltration, Solute Transport, and Root Water Uptake in Vadose Zone) was developed for simulating transient soil water flow, solute transport, and root water uptake in crops under water and salinity stress in a multilayered unsaturated soil layer. SMITUV solves the mixed form one-dimensional Richards' equation with a sink term for water transport and root water uptake and advection-diffusion equation for solute transport. It simulates salinity and water stress on root water uptake as a function of osmotic and matric potential. SMITUV is based on fundamental physical principals and is robust enough to handle different scenarios and " what-if " runs and also has tools that are crucial for growers to understand the salt-water-soil system. The model is designed to be a planning tool for strategic desalination methods and field management measures that optimize irrigation water use for flood irrigated arid region crops.